2019
DOI: 10.1111/nph.16122
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of MIKC‐type MADS‐box genes in wheat: pervasive duplications, functional conservation and putative neofunctionalization

Abstract: Summary Wheat (Triticum aestivum) is one of the most important crops worldwide. Given a growing global population coupled with increasingly challenging cultivation conditions, facilitating wheat breeding by fine‐tuning important traits is of great importance. MADS‐box genes are prime candidates for this, as they are involved in virtually all aspects of plant development. Here, we present a detailed overview of phylogeny and expression of 201 wheat MIKC‐type MADS‐box genes. Homoeolog retention is significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
200
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(238 citation statements)
references
References 133 publications
(226 reference statements)
11
200
1
Order By: Relevance
“…To provide additional context to gene function, we performed a BLASTP search using each annotated gene as a query against the NCBI NR database of proteins. We also added additional annotation information for genes encoding members of different transcription factor families [67], MIKC subclass members of the MADS-box gene family [68] and of the FT-like gene family [63]. Full information of the annotations associated with each differentially expressed gene are provided in Additional file 2.…”
Section: Methodsmentioning
confidence: 99%
“…To provide additional context to gene function, we performed a BLASTP search using each annotated gene as a query against the NCBI NR database of proteins. We also added additional annotation information for genes encoding members of different transcription factor families [67], MIKC subclass members of the MADS-box gene family [68] and of the FT-like gene family [63]. Full information of the annotations associated with each differentially expressed gene are provided in Additional file 2.…”
Section: Methodsmentioning
confidence: 99%
“…The MADS-box transcription factors analysed here using the proposed nomenclature of (Schilling et al, 2020), which are different from those we have described previously (Dixon et al, 2018b).…”
Section: Rna Extraction and Expression Analysismentioning
confidence: 97%
“…4). The result suggested that fifty of the predicted JcMADS genes were expressed in at least one of the organs examined, while thirteen (JcMADS04, 11,17,20,21,22,28,30,31,35,43,45 and 57) were not expressed in any of these tissues. Of the 50 JcMADS genes for which expression was detected, two (JcMADS03 and 53) were highly expressed across all the tissues sampled, ten (JcMADS09, 10,16,19,23,40,41,42, 56 and 58) were expressed only in seeds, thirteen (JcMADS01, 02, 05, 08, 13,29,34,40,44,51,55,60, and 63) exhibited highest expression in seeds, four (JcMADS24, 36, 48 and 49) preferred to be expressed in roots, and one (JcMADS32) was most strongly expressed in the stem cortex.…”
Section: Expression Profile Of Jcmads Genes Under Non-stressed Growthmentioning
confidence: 98%